Senyum : Psikologi Positif dan Psikologi Islam - Nurliani Firdaus; Ramli (Indonesian Journal of Islamic Counseling, 2023)
Psychology began to focus its studies not only on mental disorders but also focused on new themes, such as smiling. To grow and develop in a social environment and strengthen the feeling of family, smiling is something that must be done. Basically, a smile will create a positive aura in the form of peace towards the people in the environment around us. This research uses a literature review method, by collecting various literature and research results that are relevant to the topic discussed in this article from various different sources. The aim of this research is to find out the benefits of smiling from the perspective of positive psychology and Islamic psychology. The research results show that smiling in positive psychology and Islamic psychology actually have similarities in viewing smiles. One of the benefits studied from the two types of psychology discussed is that it can reduce stress levels in humans. In Islam itself, as we already know, a smile is interpreted as a form of worship in the form of alms which is the easiest to do. Smiling also turns out to bring various positive impacts and huge benefits. One of the benefits of smiling is reducing stress levels.